2017
DOI: 10.1017/s1049096517000014
|View full text |Cite
|
Sign up to set email alerts
|

Negating the Gender Citation Advantage in Political Science

Abstract: Open-access (OA) advocates have long promoted OA as an egalitarian alternative to traditional subscription-based academic publishing. The argument is simple: OA gives everyone access to high-quality research at no cost. In turn, this should benefit individual researchers by increasing the number of people reading and citing academic articles. As the OA movement gains traction in the academy, scholars are investing considerable research energy to determine whether there is an OA citation advantage—that is, does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…While digital humanities is increasingly concerned with opening our scholarship, our main journal remains paywalled. This tension is further exacerbated by citation research that suggests that open access practices make citations more egalitarian (Atchinson, 2017). In the future, it would be interesting to look at this, though it is outside the scope of our current work.…”
Section: Discussionmentioning
confidence: 94%
“…While digital humanities is increasingly concerned with opening our scholarship, our main journal remains paywalled. This tension is further exacerbated by citation research that suggests that open access practices make citations more egalitarian (Atchinson, 2017). In the future, it would be interesting to look at this, though it is outside the scope of our current work.…”
Section: Discussionmentioning
confidence: 94%
“…This surface-level representation is based upon the visibility of women and gender in course readings, as well as the essential recognition that there is more than one gender (Burnier, 2005; Guy, 2010; Hewins-Maroney and Williams, 2007; McGinn and Patterson, 2005; Stivers, 2005; White, 2004; White Perry, 2005). The inclusion of multiple genders is further emphasized by research showing that students, and particularly women and minority students, are empowered when they see reflections of themselves in course scholarship (Burnier, 2005; Lane, 2014), and, conversely, are negatively impacted through internalized feelings of being ignored or an outsider when there is no reflection opportunity (Atchison, 2017; Braun et al, 2017; Coryat and Clemens, 2017). The lack of visibility of women (or minorities and other underrepresented groups in the discipline) reinforces a status quo power dynamic that traditionally represents a mono-cultural, Eurocentrist, male-dominated emphasis (Bondy et al, 2015; Feeney et al, 2019; Lane, 2014; Samanta, 2015).…”
Section: The Diversity Inclusion Model: Gendermentioning
confidence: 99%
“…However, a far more flexible tool for incorporating visibility and reflection opportunities for multiple genders is through the inclusion of assigned reading materials. Recent studies have found an underrepresentation of female authors being assigned in course syllabi (Evans, 2018; Hatch, 2018), and isolated or marginalized within textbooks (Atchison, 2017). These findings are concerning, particularly given the emphasis on public service values of inclusion and diversity within public administration.…”
Section: The Diversity Inclusion Model: Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the evidence that female authors tend to receive fewer citations than men in some academic disciplines (Aksnes et al 2011, Maliniak et al 2013, Beaudry and Larivière 2016, Atchison 2017, there is little evidence for gender bias in acceptance or citation rates of ecology papers. In one regional ecology journal (New Zealand Journal of Ecology), publication success between 2003 and 2012 was not related to the gender of the authors or that of the editor, but like Functional Ecology, editors selected more male reviewers (Buckley et al 2014), likely because there are simply more male ecologists from which to choose reviewers.…”
Section: Introductionmentioning
confidence: 96%